The structure-based mechanism of translation initiation in bacteria and eukaryotes - Kieft, Jeffrey (Henry Stewart Talks, 2008)
Importance, principles and pathways of translation initiation, Components of initiation in bacteria, The Shine-Dalgarno sequence, Structures and function of bacterial initiation factors, Complexity of eukaryotes initiation, Cap recognition and regulation, Structures of eukaryotic initiation factors, Update interview: Impact of new structural information, Update interview: Evolution and robustness of existing models, Update interview: Need to understand dynamic processes
Updated at 2020/11/30